Litogeochemistry of metabasites from the Moura Phyllonitic Complex (Ossa Morena Zone, SW Portugal) - Roseiro, José (2020)
Several metabasites were sampled for major and trace element ICP-OES analysis (prepared with alkaline fusion, acid digestion and cation-exchange chromatography), in order to characterize their geochemical variability and attempt to correlate with other autochthonous volcanic rocks, thus inferring their geodynamic setting.